PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN IPA DI SEKOLAH MENENGAH PERTAMA (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractResearch has conducted to purpose designing, developing, dan producing the comics as a medium of science learning in junior high school. Design, development, and produced of comics has done by using a modified model of ADDIE. To determine the feasibility and usefull of products, validation and limited testing has performed. Validation is done by experts to assess aspects of simplicity, emphasis, balance, alignment, and design of the comic. Limited testing conducted on students grade VII and VIII SMPN 1 Pekanbaru. The results of the validation by 5 experts claim that comics produced valid for use (mean score 3.13). Likewise with limited trial against the students of SMPN 1 Pekanbaru, the student stated comics produced excellent for use in the learning process (score 95.42). Based on the results of validation and limited testing, the comics that have been produced can be an alternative as a medium of learning in junior high school.Keywords: Comics, Medium of Science Learning, Innovation Learning